HLA-E regulatory and coding region variability and haplotypes in a Brazilian population sample - Ramalho, Jaqueline [UNESP]; Veiga-Castelli, Luciana C.; Donadi, Eduardo A.; Mendes-Junior, Celso T.; Castelli, Erick C. [UNESP] (Elsevier, 2017)
The HLA-E gene is characterized by low but wide expression on different tissues. HLA-E is considered a conserved gene, being one of the least polymorphic class I HLA genes. The HLA-E molecule interacts with Natural Killer cell receptors and T lymphocytes receptors, and might activate or inhibit immune responses depending on the peptide associated with HLA-E and with which receptors HLA-E interacts to. Variable sites within the HLA-E regulatory and coding segments may influence the gene function by modifying its expression pattern or encoded molecule, thus, influencing its interaction with receptors and the peptide. Here we propose an approach to evaluate the gene structure, haplotype pattern and the complete HLA-E variability, including regulatory (promoter and 3′UTR) and coding segments (with introns), by using massively parallel sequencing. We investigated the variability of 420 samples from a very admixed population such as Brazilians by using this approach. Considering a segment of about 7 kb, 63 variable sites were detected, arranged into 75 extended haplotypes. We detected 37 different promoter sequences (but few frequent ones), 27 different coding sequences (15 representing new HLA-E alleles) and 12 haplotypes at the 3′UTR segment, two of them presenting a summed frequency of 90%. Despite the number of coding alleles, they encode mainly two different full-length molecules, known as E*01:01 and E*01:03, which corresponds to about 90% of all. In addition, differently from what has been previously observed for other non classical HLA genes, the relationship among the HLA-E promoter, coding and 3′UTR haplotypes is not straightforward because the same promoter and 3′UTR haplotypes were many times associated with different HLA-E coding haplotypes. This data reinforces the presence of only two main full-length HLA-E molecules encoded by the many HLA-E alleles detected in our population sample. In addition, this data does indicate that the distal HLA-E promoter is by far the most variable segment. Further analyses involving the binding of transcription factors and non-coding RNAs, as well as the HLA-E expression in different tissues, are necessary to evaluate whether these variable sites at regulatory segments (or even at the coding sequence) may influence the gene expression profile.
Keywords: HLA-E, 3′ untranslated region; Next generation sequencing; Polymorphism; Promoter; Variability